Exploring the perception of nutrition among collegiate sports enthusiasts in a public university in Selangor, Malaysia - Sun, He; Tengku Kamalden, Tengku Fadilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
The sports nutrition field is an exponential increase in recent years. Especially, athletes use it to optimize the performance in competition and normal training, which recommendations can be adjusted by team dietitians. However, the population of collegiate sports enthusiasts is increasing. Usually, dietitians for them are unavailable. So, explore their overall perception of nutrition is important. The purpose of this study is to explore the collegiate sports enthusiasts' perception of nutrition on physical exercise. Semi-structure interviews were applied to the sample. Four University Putra Malaysia students who are sports enthusiasts involved in the study. Data Analysis: The grounded theory method was used to analyze data. Code and classify the data, some themes emerged gradually. Accessibility and knowledge are primary themes to show the perception of nutrition affect physical exercise. Some subthemes further evaluate the collegiate sports enthusiasts' perspectives and perceptions, which include utilization, understanding, resource, and cost related to knowledge and accessibility respectively. Collegiate sports enthusiasts believed nutrition plays a key role in their overall health. However, there was a significant gap between nutritional decisions and available conditions on campus, but also a gap in how they apply the knowledge to improve body health and performance in sports. Thus, extra nutritional education and professional guideline are necessary.